A corrected type designation for Lophozonia heterocarpa, with an update on the lectotype of Fagus obliqua (≡ Nothofagus obliqua, Lophozonia obliqua) (Nothofagaceae) - Mosyakin, Sergei L.; Sokolova, Irina V.; Tatanov, Ivan V. (Phytotaxa, 2019)
A corrected type designation for the name Lophozonia heterocarpa Turcz. (now accepted either as L. obliqua or Nothofagus obliqua) is provided; this name is the type of Lophozonia Turcz. recently proposed to be taxonomically restored as a genus segregated from Nothofagus sensu lato. The specimen from the Turczaninow historical herbarium at KW annotated by Turczaninow is considered to be the holotype because it has been explicitly stated in the protologue that the description of L. heterocarpa, as well as those of other taxa in that publication, were based on specimens (holotypes or syntypes) from Turczaninow’s personal herbarium, now held in KW. The specimen from LE previously designated as the lectotype is corrected to isotype since it is a duplicate of the holotype from KW. Digital images of the holotype (KW) and isotype (LE) of L. heterocarpa are provided. Three other isotypes are known in E and K herbaria. It is also demonstrated that the lectotype of Fagus obliqua Mirb. (the basionym of Nothofagus obliqua and Lophozonia obliqua) was cited by Vásquez & Rodíguez in 1999 precisely enough to distinguish it from three other specimens in P also collected by Dombey in Chile. Thus, despite the presence of four duplicates in P, no second-step lectotypification is needed.